Metabolic adaptations of Escherichia coli to extended zinc exposure: insights into tricarboxylic acid cycle and trehalose synthesis - Rihacek, Martin; Kosaristanova, Ludmila; Fialova, Tatiana; Rypar, Tomas; Sterbova, Dagmar Skopalova; Adam, Vojtech; Zurek, Ludek; Cihalova, Kristyna (BMC microbiology, 2024)
Balanced bacterial metabolism is essential for cell homeostasis and growth and can be impacted by various stress factors. In particular, bacteria exposed to metals, including the nanoparticle form, can significantly alter their metabolic processes. It is known that the extensive and intensive use of food and feed supplements, including zinc, in human and animal nutrition alters the intestinal microbiota and this may negatively impact the health of the host. This study examines the effects of zinc (zinc oxide and zinc oxide nanoparticles) on key metabolic pathways of Escherichia coli. Transcriptomic and proteomic analyses along with quantification of intermediates of tricarboxylic acid (TCA) were employed to monitor and study the bacterial responses. Multi-omics analysis revealed that extended zinc exposure induced mainly oxidative stress and elevated expression/production of enzymes of carbohydrate metabolism, especially enzymes for synthesis of trehalose. After the zinc withdrawal, E. coli metabolism returned to a baseline state. These findings shed light on the alteration of TCA and on importance of trehalose synthesis in metal-induced stress and its broader implications for bacterial metabolism and defense and consequently for the balance and health of the human and animal microbiome.
Keywords: Virulence; Trehalose; Gene Expression Regulation, Bacterial; Metabolic Networks and Pathways; oxidační stres; Escherichia coli; citrátový cyklus; Nanoparticles; Oxidative Stress; Proteome; Citric Acid Cycle; metabolické sítě a dráhy; Carbohydrate metabolism; Trehalose synthesis; Zinc; proteomika; fyziologická adaptace; oxid zinečnatý; proteiny z Escherichia coli; stanovení celkové genové exprese; regulace genové exprese u bakterií; Zinc Oxide; zinek; Proteomics; Tricarboxylic acid cycle; Zinc oxide; Adaptation, Physiological; transkriptom; Transcriptome; trehalosa; Gene Expression Profiling; Escherichia coli Proteins